The Influence of Brand Image, Price Perception, Brand Awareness on Brand Loyalty (Study on Wardah Facial Cleanser Customers) - Puspasari, Fitri Diana; Utama, Andyan Pradipta (Universitas Mercu Buana, 2024)
The research aims to determine the effect of brand image, price perception, brand awareness on brand loyalty (study on wardah facial cleanser customers). This research was conducted on 185 respondents using a quantitative approach. The data analysis method used is Structural Equation Modelling (SEM). The results showed that brand image has a positive and significant effect on wardah facial cleanser brand loyalty, price perception has a positive and significant effect on wardah facial cleanser brand loyalty, brand awareness has a positive and significant effect on wardah facial cleanser brand loyalty.